CLINICAL CASE. EPIDERMOLYSIS BULLOSA OF KINDLER (KINDLER SYNDROME) - M.R. Rysuly; S.A. Ospanova; A.A. Taubaeva; Z.M. Sukhanberdiyeva; A.S. Idrisova; U.T. Zharylkap (Interdisciplinary Science Studies, 2024)
Epidermolysis bullosa (EB) is a genodermatosis that encompasses a group of clinically and genetically heterogeneous diseases classified into four main types: simple EBE (SEB), borderline EB (BordEB), dystrophic EB (DEB), and Kindler's EB syndrome. All forms of Congenital EB are associated with genetically determined structural abnormalities of proteins somehow related to the epidermo-dermal connection of the skin - mutations of genes encoding these proteins. The main clinical manifestation is the exceptional fragility of the skin - at the slightest physical impact is the formation of blisters and the appearance of bullous elements. In most cases, the disease is inherited by autosomal recessive type, however, cases of somatic mosaicism and single-parent dysomy have been described. Mutations in the COL7A1 gene have been described in DEB, in 95% of cases of dominant and recessive types of EB.